Raw ingredients in cat food manufacturing : palatability, digestibility and halal issues in Malaysia - Amir Husni Mohd Shariff; Mona, Z. (Universiti Malaysia Kelantan, 2013)
Raw ingredients commonly used in the cat food manufacturing are derived from various sources such as meat, meat by products, fish, poultry, vegetables, vegetables by products, cereals, fruits, and bones. Meat meal and meat bone meal are unpopular raw ingredients since they are manufactured from carcasses and offal of cows, pigs, goats and sheep and may even contain deleterious and unhealthy ingredients. There is the possibility of the occurrence of ingredients containing non halal components. There are several types of cat food in the market which are graded based on their ingredients and nutritive values especially the protein content. The biological values of the popular protein sources used in cat food manufacturing were highlighted. The importance of carbohydrate content, which is mostly not available on the packaging pack is emphasized and the method of calculation shown.